2013
DOI: 10.1007/s00441-013-1633-7
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular transfer of membrane components to bovine epididymal spermatozoa

Abstract: Epididymosomes (apocrine secreted epididymal vesicles) are assumed to play a crucial role in sperm maturation. Our aim has been to analyze the fusogenic properties of bovine epididymosomes and their involvement in the transfer of membrane components (lipids, proteins, plasma membrane Ca(2+)-ATPase 4 [PMCA4]) into bovine sperm. The fusogenic properties of epididymosomes with spermatozoa were investigated in vitro by using octadecyl rhodamine-B (R18)-labeled epididymosomes. Spermatozoa isolated from the epididym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
8
39
0
Order By: Relevance
“…Similar findings were obtained for bovine sperm and epididymosomes (19), and OVS were also shown to deliver PMCA4 in vitro to murine sperm (6). In this study, we show co-immunolocalization of PMCA4 and fluorescently-labeled OVS that were fused to the sperm surface, providing evidence that OVS deliver their cargo via fusion.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar findings were obtained for bovine sperm and epididymosomes (19), and OVS were also shown to deliver PMCA4 in vitro to murine sperm (6). In this study, we show co-immunolocalization of PMCA4 and fluorescently-labeled OVS that were fused to the sperm surface, providing evidence that OVS deliver their cargo via fusion.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, Schwarz et al (19) proposed a fusogenic mechanism for the transfer of PMCA4 from epididymosomes to bovine sperm, although the molecular basis underlying the process was not investigated (19). While exosomes/microvesicles are known to carry adhesion molecules such as tetraspanin (CD9 and CD81), which build fusion-competent sites (20,21), and integrins which play a potential role in cell-to-cell communication (22), the mechanism of their action in cargo delivery remains unknown (23,24).…”
mentioning
confidence: 99%
“…As fructose is a major energy source for spermatozoa, these enzymes may play an important role in sperm cell motility (Frenette et al 2006). In a recent study, in vitro fusion of isolated epididymosomes with sperm was reported (Schwarz et al 2013), presumably explaining how epididymal epithelial cell cytosolic and membrane constituents can be integrated into sperm cells. Sperm capture of epididymosomes is apparently quite efficient, or epididymosomes are subsequently recaptured by epididymal epithelial cells, as the contribution of nonsperm associated free epididymosomes to the total population of EVs in the ejaculate appears to be low.…”
Section: Evs In the Male Reproductive Tractmentioning
confidence: 99%
“…The fusogenic properties of bovine epididymosomes with spermatozoa were investigated by Schwarz et al who observed that spermatozoa isolated from the epididymal caput showed a higher fusion rate (both pH and time dependent) than those taken from the cauda (Schwarz et al, 2013). Also, the lipid and protein content in spermatozoa changed during epididymal transit and after in vitro fusion with epididymosomes.…”
Section: The Crosstalk Between Epithelial Cells and Spermatozoa Durinmentioning
confidence: 99%